Massive star formation: the role of disks - Fallscheer, Cassandra Lorlene (2010)
In this thesis, I study three different evolutionary stages of the massive star formation process looking for supporting evidence for an accretion-based formation scenario of massive stars. The first source studied, the Infrared Dark Cloud IRDC 18223-3, is at one of the earliest observable phases of massive star formation. This source is characterized by a cone-shaped molecular outflow component which is used to establish the outflow orientation. A velocity gradient traced by the molecule N2H+ but more convincingly by CH3OH is indicative of a rotating object oriented orthogonally to the outflow direction. This object is on the order of 28,000 AU in size and does not exhibit Keplerian rotation, but may host a disk within. Modeling this velocity gradient shows that a single rotating and infalling entity is capable of reproducing the observations. Moving to a High Mass Protostellar Object, IRAS 18151-1208, a well-defined outflow orientation is observed as well as an elongation in the 1.3 millimeter dust continuum that is perpendicular to the outflow. This elongation is modeled using a Monte Carlo 3D radiative transfer code. Comparing the modeling results to those of low mass protostars it is deduced that a scaled up version of low-mass star formation provides a plausible description of the observations in this high mass case. In the scaled up version, the density and flaring exponents as well as the relative scale height at one third of the outer radius remain the same as in the low-mass model. The disk mass, outer radius, and central star's mass and luminosity all increase ...
Online publiziert: 2010
Keywords: Hochschulschrift; Akkretionsscheibe; Spektroskopie; Interferometrie; Sternentstehung